The potential of integrating conscious living into education for generation Z in the light of primary data - Garai-Fodor, Mónika; Huszák, Nikolett (Frontiers in Education, 2025)
IntroductionIn this study, we investigate the cognitive aspects of conscious consumer behaviour among Generation Z members. We argue that conscious consumption can greatly help to foster social responsibility, environmental and health-conscious behaviour and ethical consumerism. We believe that it is an important educational task to promote and reinforce consumer behaviour among young people that increases and creates community value.MethodsIn this study, we analysed the dimensions of young people’s conscious consumer behaviour and its manifestation in concrete forms of behaviour, purchasing and consumer decisions. The primary research used a pre-tested standardised questionnaire online survey using a snowball sampling technique. Data were evaluated using bivariate and multivariate analyses in addition to descriptive statistics.ResultsThe results allowed us to identify exactly what conscious living means to young people, what behavioural elements they associate with it and what activities they themselves carry out in this context. The results show that conscious living among young people is most closely linked to healthy lifestyle activities and is closely related to good self-awareness.DiscussionThe results show that the vast majority of the Generation Z respondents surveyed do not have a realistic picture of themselves in terms of a conscious lifestyle, although self-awareness and self-identity can be seen as the basis of a conscious lifestyle. Therefore, we believe that there is a great need to adequately integrate conscious living into education. Authentic, targeted education campaigns for Generation Z can best help to equip young people with the right self-awareness and the right information about conscious living.